An Overview on the Transpersonal Art Therapy (International Journal of Innovative Research in Engineering & Management, 2021)
The beginning of recorded history, it has been known that human  people have utilized art to express elements that transcend the  spoken and the written word, in order to convey the condition of  their inner mental landscapes. Art is inherently healing and has  the power to change. Transpersonal Art Therapy takes one step  beyond conventional art therapy and digs into soul of the  individual beyond the boundaries of his/her personal identity.  This article offers a systematic assessment of the literature,  pointing out the merits, critiques, and subsequently, the first  author’s own personal thoughts about connection with art. This is  followed by introspective thoughts on art movements, by giving  quintessential instances to demonstrate the effect of prototype  work representing various art movements and their impact on the  irst author’s psychology. Future ramifications of the study are  addressed along with areas in which there are large gaps in  empirical data, which thus need to be studied. Transpersonal art  therapy is both a method of thinking and a way of doing things. It  recognizes spirituality as universal across nations and history,  compelling to include spiritual in scope evaluation and treatment,  and pushes us to strive for a balance of mind, body, emotions, and  spirit in everyone treat, beginning with ourselves.
Keywords: Art; Human; Life; Therapy; Transpersonal